1994
DOI: 10.1897/1552-8618(1994)13[529:rbavsa]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Acid Volatile Sulfide and the Toxicity of Zinc, Lead and Copper in Marine Sediments

Abstract: It has been proposed that acid volatile sulfide (AVS) is an important sediment phase for determining the toxicity of certain trace metals. By evaluating the ratio of the molar quantities of simultaneously extracted metal (SEM) to AVS, the toxicity of metals to organisms in contact with sediment can be predicted. This study examines the role of AVS in predicting the toxicity of zinc, lead, and copper in marine sediments. Sediment samples were titrated with zinc, lead, and copper and subsequently analyzed for SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
40
0
3

Year Published

1994
1994
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 10 publications
6
40
0
3
Order By: Relevance
“…AVS can assess the potential risks of heavy metals correctly with the further advantages such as high efficiency, simple utilization, and batch processing (Allen et al 1993;Brouwer and Murphy 1994;De Lange et al 2008). AVS is considered as one of the main chemical constituents of marine sediments that plays a significant role in controlling the speciation and the environmental risks of heavy metals in the sediments and its interstitial waters (Casas and Crecelius 1994;Cooper and Morse 1998;Prica et al 2008), while simultaneously extracted metals (SEMs) refers to sulfide-bound metals extracted in the AVS extraction procedure (mostly including copper (Cu), cadmium (Cd), lead (Pb), nickel (Ni), and zinc (Zn)) (Di Toro et al 1990;Li et al 2014a). In ecosystem studies, the sum of the molar concentrations of SEM (μmol/g) in comparison with AVS (μmol/g) was suggested as an important indicator to evaluate the bioavailability and potential ecological risk of heavy metals (Berry et al 1996;Di Toro et al 1990).…”
Section: Introductionmentioning
confidence: 99%
“…AVS can assess the potential risks of heavy metals correctly with the further advantages such as high efficiency, simple utilization, and batch processing (Allen et al 1993;Brouwer and Murphy 1994;De Lange et al 2008). AVS is considered as one of the main chemical constituents of marine sediments that plays a significant role in controlling the speciation and the environmental risks of heavy metals in the sediments and its interstitial waters (Casas and Crecelius 1994;Cooper and Morse 1998;Prica et al 2008), while simultaneously extracted metals (SEMs) refers to sulfide-bound metals extracted in the AVS extraction procedure (mostly including copper (Cu), cadmium (Cd), lead (Pb), nickel (Ni), and zinc (Zn)) (Di Toro et al 1990;Li et al 2014a). In ecosystem studies, the sum of the molar concentrations of SEM (μmol/g) in comparison with AVS (μmol/g) was suggested as an important indicator to evaluate the bioavailability and potential ecological risk of heavy metals (Berry et al 1996;Di Toro et al 1990).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the simultaneously extracted metals -acid volatile sulfide (SEM-AVS) method is an effective tool in predicting the absence of metal toxicity in sediments in short-term toxicity tests when [SEM-AVS] < 0 (Di Toro et al, 1990;Di Toro et al, 1992;Casas and Crecelius, 1994;Pesch et al, 1995;Hansen et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The pore water hypothesis predicts that, if the molar concentration of simultaneously extracted metals (SEM) in a sediment is smaller than the molar concentration of AVS, the free metal ion activity in the pore water is very small and that consequently no metal toxicity in short-term toxicity tests is observed. In this study we examined (1) if this concept can be extended to predict the absence of chronic Ni toxicity to the oligochaete deposit-feeding worm Lumbriculus variegatus and (2) It has been demonstrated that the simultaneously extracted metals -acid volatile sulfide (SEM-AVS) method is an effective tool in predicting the absence of metal toxicity in sediments in short-term toxicity tests when [SEM-AVS] < 0 (Di Toro et al, 1990;Di Toro et al, 1992;Casas and Crecelius, 1994;Pesch et al, 1995;Hansen et al, 1996).The underlying principle is that except for pyrite, all other iron and manganese mono sulfides that may be present in sediments have higher solubility products than other metal sulfides. Thus, Fe and Mn can be displaced by other divalent metals (Cu, Cd, Ni, Pb, Zn) on a mole-to-mole basis.…”
mentioning
confidence: 99%
“…All interstitial waters procedures were carried out under nitrogen atmosphere. Another portion of wet sediments was stored under a nitrogen atmosphere for determination of acid-volatile sulfide (AVS) by linear sweep voltammetry, as described by Casas and Crecelius (1994). The sea bass specimens, of %20 cm length, were dissected and the muscle tissue separated.…”
mentioning
confidence: 99%